A link between severe hepatitis in children and adenovirus 41 and adeno-associated virus 2 infections. (11th November 2022) - Grand, Roger J
Abstract : Over the past few months there have been reports of severe acute hepatitis in several hundred, otherwise healthy, immunocompetent young children. Several deaths have been recorded and a relatively large proportion of the patients have needed liver transplants. Most of the cases, so far, have been seen in the UK and in North America, but it has also been reported in many other European countries, the Middle East and Asia. Most common viruses have been ruled out as a causative agent; hepatitis A virus (HAV), hepatitis B virus (HBV) and hepatitis C virus (HCV) were not detected, nor were Epstein–Barr virus (EBV), cytomegalovirus (CMV) and human immunodeficiency virus (HIV) in many cases. A small proportion of the children had been infected with SARS-CoV-2 but these seem to be in a minority; similarly, almost none of the children had been vaccinated against COVID-19. Significantly, many of the patients were infected with adenovirus 41 (HAdV-F41). Previously, HAdV-41 had not been linked to hepatitis and is usually considered to cause gastroenteritis in both immunocompetent and immunocompromised patients. In two most recent studies, adeno-associated virus 2 (AAV2) was detected in almost all patients, together with species C and F HAdVs and human herpesvirus 6B (HHV6B). Here, I discuss the possibility that a change in tropism of HAdV-41 and changes in AAV2 may be responsible for their links to acute hepatitis.